Characteristic compressive strength correlation of rubberized concrete interlocking masonry wall. (August 2020) - Al-Fakih, Amin; Mohammed, Bashar S.; Wahab, M.M.A.; Liew, M.S.; Mugahed Amran, Y.H.; Alyousef, Rayed; Alabduljabbar, Hisham
Abstract: The rapid growth in the construction industry has dictated the utilisation of the eco-friendly materials and recycling of wastes to produce sustainable products. In this study, rubberized concrete interlocking bricks have been developed by utilising crumb rubber (10%) and fly ash (56%) as partial replacements of sand and OPC, respectively. It is aimed to develop mean and characteristic compressive strength correlations of rubberized concrete interlocking hollow and grouted wall systems, corresponding to rubberized concrete interlocking brick and prism strengths. A systematic investigation of 20 rubberized concrete interlocking brick units, 10 hollow and grouted rubberized concrete interlocking prisms and 10 identical hollow and grouted rubberized concrete interlocking wall panels were cast, constructed and tested under compressive load. Results were statistically analysed and the design-charts for the mean and characteristic compressive strength of masonry were used. The results obtained for the strength of rubberized concrete interlocking brick, prism and wall revealed a normal distribution with 5% significant interval. Four types of regression models were proposed for statistical analysis and the best fit model was identified based on r 2 (correlation coefficient). The power model for the mean and characteristic strength curves presented the best fit to the sorted data. The cracking pattern and modes of failure of the tested specimens were discussed. The relationships for characteristic strengths of rubberized concrete interlocking masonry hollow and grouted wall were derived in terms of rubberized concrete interlocking unit and prism strength and found to be fkw  = 1.533 fb 0.290, fkw  = 2.178 fb 0.337 and fkw  = 1.119 fp 0.659, fkw  = 1.023 fp 0.731, respectively.